CT-guided biopsy of the mediastinal masses. Can anatomical relationships predict complications? - Dvorak, Petr; Hoffmann, Petr; Kocova, Eva; Habal, Petr; Nova, Marketa (Biomedical papers, 2019)
Aim: To retrospectively evaluate the technical features, feasibility, efficacy, accuracy and appropriate complications of CT-guided biopsies of mediastinal masses and correlate them with anatomical relationships in the mediastinum. Methods: Over the course of ten years, 81 percutaneous biopsy procedures in 78 patients for tumors sizes 27 - 189 mm in diameter (median length 57.5 mm) were performed using only local anesthesia. These interventions were done under the guidance of computed tomography. The patients were men in 30 cases and women in 48 cases, aged 19 to 90 years. Results: In 78 cases (96.3%) results were either true positive or true negative; in only 3 cases (3.7%, 3 biopsies of 2 tumors in 2 patients) were histological findings false negative. In 2.3% of the patients, complications were revealed in the anterior part of the mediastinum, 43.7% occurred in the middle region, and 14.3% in the posterior region of the mediastinum. Statistical data analysis verified there was a 3.74 times chance of an increase in complications in the middle mediastinal section in correlation with other anatomical localizations. In only one case was therapeutic intervention for complication necessary. For all other cases, a conservative approach was suitable. Conclusion: Percutaneous CT guided biopsies of the mediastinal tumors has a high accuracy rate in establishing the correct diagnosis. Masses in the middle mediastinum are associated with statistically higher incidences of postprocedural complications, which are not serious.
Keywords: percutaneous biopsy; mediastinal tumors; minimally invasive diagnosis; biopsy complications